A Coordinated, Risk-Based, National Forest Biosecurity Surveillance Program for Australian Forests - Carnegie, Angus J.; Tovar, Francisco; Collins, Susie; Lawson, Simon A.; Nahrung, Helen F. (Frontiers in Forests and Global Change, 2022)
Australia has a comprehensive plant biosecurity system, with the Australian Government responsible for pre-border (e.g., off-shore compliance) and border (e.g., import inspections) activities, while state governments undertake a variety of post-border activities (e.g., post-border surveillance, management of pest incursions, and regulation of pests) designed to reduce alien pest and pathogen arrival and establishment. Once an alien pest or pathogen has established and spread, its management becomes the responsibility of the land manager. There has been a growing understanding among plant industries of the need to be more engaged in post-border biosecurity activities, including resourcing and undertaking early detection surveillance and contingency planning. Here we summarize Australia’s broader plant biosecurity system along with current forest-specific biosecurity surveillance activities. We describe the development of a proposed forest biosecurity partnership between the Australian Government, state governments and the forest sector to establish a post-border, risk-based National Forest Pest Surveillance Program. We outline why there is a recognized need for such a program, how it would improve biosecurity outcomes in relation to forests, its component activities, and key stakeholders and beneficiaries.